Evaluation of stress hormones on reproductive functions of sheep and goats: a systematic review - Tada, Obert; Tshabuse, Phillip Masilo; Mamakoko, Mojakgomo Sidney; Mashamaite, Puleng Kgabo (Frontiers in Animal Science, 2025)
In the face of climate variability and resource limitations, stress-related hormonal disruptions challenge the sustainability and reproductive performance of small ruminants. This systematic review evaluated the impact of key stress hormones such as cortisol, adrenaline, and glucocorticoids on reproductive functions of sheep and goats. A comprehensive search of databases including PubMed, ScienceDirect, Web of Science, and Google Scholar yielded 29 eligible peer-reviewed articles published between 2005 and 2024. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and Population, Intervention, Comparison, Outcome (PICO) tools were employed for evidence-based practice ensuring a rigorous and transparent manner in conducting and reporting this research. The Cochrane Risk of Bias instrument was adopted to assess data quality and biasness of the included studies. The results consistently indicated elevated stress hormone levels impair the hypothalamic-pituitary-gonadal axis, leading to delayed ovulation, reduced conception rates, irregular estrous cycles, and compromised sperm quality. Major environmental factors contributing to hormonal imbalance identified were heat stress, nutritional deficiencies, inappropriate handling, social instability, and diseases. Additionally, genetic variation among breeds influenced the severity of stress responses. However, the limited African-based research and inconsistent reporting of environmental conditions highlight critical knowledge gaps. This review emphasizes the need for climate-resilient and welfare-oriented livestock strategies meant to mitigate stress and enhance reproductive outcomes in sheep and goats.